Effects of nitrogen nutrient on the behavior of feeding and oviposition of the brown planthopper, Nilarpavata lugens, on IR64 - LÜ Zhong-xian; YU Xiao-ping; HEONG Kong-luen; HU Cui (浙江大学学报. 农业与生命科学版)
We determined the preferences of feeding and oviposition of the brown planthopper (BPH), Nilaparvata lugens, to rice plants of IR64 with different nitrogen content, the changes in preferences of BPH populations fed successively on plants with high (200N) or low (0N) nitrogen fertilizer, and the influences of nitrogen content on the spatial distribution patterns of feeding and oviposition. In choice test, all females from four populations reared on both 200N and 0N rice plants preferred significantly to feed and oviposite on plants with high nitrogen content, while no marked difference in nymph feeding preference was found among the rice plants. The positions of feeding and oviposition were shifted gradually from the bottom to upper of leaf sheath, and then to leaf blade with the reduction of nitrogen content in host plants. Both nymphs and adults located at higher position of plants and fed much more frequently on 0N rice plants than that on 200N rice plants, and differed markedly among BPH populations. The highest feeding frequency was found in the nymphs, which reared successively on 0N rice plants, on 0N rice plants, implying that feeding frequencies of BPH populations were related closely to their previous host plants.